Is life skill development a by-product of sport participation? Perceptions of youth sport coaches - Bean, Corliss; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2016)
The purpose of this study was to understand youth sport coaches’ perceptions of life skill development. Semi-structured interviews were conducted with 23 youth sport coaches across five organizations. Analyses revealed four themes based on coaches’ perceptions: (a) life skills are a by-product of sport participation and transfer ‘just happens’; (b) if intentionally addressed, it’s reactive; (c) coaches recognize the value of intentionally teaching life skills; and (d) challenges associated with using an explicit approach to teaching life skills. Results provide evidence for the state of the current sport context and highlight areas for coach education related to life skills integration.
Keywords: Positive Youth Development; life skills, sport; coaches; intentionality; qualitative methods